Quantifying the Mortality Impact of Do-Not-Resuscitate Orders in the ICU - Fuchs, L.; Anstey, Matthew; Feng, M.; Toledano, R.; Kogan, S.; Howell, M.; Clardy, P.; Celli, L.; Talmor, D.; Novack, V. (Lippincott Williams & Wilkins, 2017)
Copyright © by 2017 by the Society of Critical Care Medicine and Wolters Kluwer Health, Inc. All Rights Reserved.OBJECTIVES:: We quantified the 28-day mortality effect of preexisting do-not-resuscitate orders in ICUs. DESIGN:: Longitudinal, retrospective study of patients admitted to five ICUs at a tertiary university medical center (Beth Israel Deaconess Medical Center, BIDMC, Boston, MA) between 2001 and 2008. INTERVENTION:: None. PATIENTS:: Two cohorts were defined: patients with do not resuscitate advance directives on day 1 of ICU admission and a control group comprising patients with no limitations of level of care on ICU day 1 (full code). MEASUREMENTS AND MAIN RESULTS:: The primary outcome was mortality at 28 days after ICU admission. Of 19,007 ICU patients, 1,239 patients (6.5%) had a do-not-resuscitate order on the first day of ICU admission and survived 48 hours in the ICU. We matched those do-not-resuscitate patients with 2,402 patients with full-code status. Twenty-eight day and 1-year mortality were both significantly higher in the do-not-resuscitate group (33.9% vs 18.4% and 60.7% vs 40.2%; p < 0.001, respectively). CONCLUSION:: Do-not-resuscitate status is an independent risk factor for ICU mortality. This may reflect severity of illness not captured by other clinical factors, but the perceptions of the treating team related to do-not-resuscitate status could also be causally responsible for increased mortality in patients with do-not-resuscitate status.